2009
DOI: 10.1007/s11517-009-0478-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound array designs for high intensity focused treatment of prostate cancer and benign prostatic hyperplasia

Abstract: This paper describes the optimization of designing a two-dimensional (2-D) ultrasound phased array to be used for the treatment of both prostate cancer and benign prostatic hyperplasia. The optimization study took into consideration the physical constraints of the conventional method of treatment, and arrived at an optimized array design with the overall dimensions of 10 cm x 2.2 cm. The optimization study also addressed the following additional parameters: The maximum possible depth of penetration (DOP), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…In the literature, acceptable side lobe levels have been variously given as 10% intensity (−10 dB) [21], 20% intensity (−7 dB) [42], or 10 to 16% intensity (−10 to −8 dB) [25] in homogeneous media. The temperature ratio in this work was shown to be 0.12 at the distal half-intensity axial depth for the 256-randomized-element case (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, acceptable side lobe levels have been variously given as 10% intensity (−10 dB) [21], 20% intensity (−7 dB) [42], or 10 to 16% intensity (−10 to −8 dB) [25] in homogeneous media. The temperature ratio in this work was shown to be 0.12 at the distal half-intensity axial depth for the 256-randomized-element case (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The biological influence of LFU and microbubbles on cancer cells is dependent on the microbubble density, ultrasound intensity and irradiation time ( 34 , 35 ). Generally, a pilot experiment should be prepared to debug the optimized ultrasound parameters, so as to induce cell apoptosis to the maximum extent ( 36 , 37 ). Studies have identified that microbubbles enhance ultrasound exposure by decreasing the cavitation threshold ( 27 ), which induces cancer cell apoptosis ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…44 Different studies have been conducted for the application of HIFU in the treatment of uterine fibroids, in the palliative treatment of pain from bone metastases, and in the treatment of prostate cancer and BPH. [45][46][47] In HIFU, frequencies of 0.8-4 MHz with intensities between 400-10 000 W/cm 2 are used, unlike conventional diagnostic ultrasound, which works at frequencies between 2-15 MHz and intensities of 0.004-7.5 W/cm 2 . The mechanical waves of the HIFU are concentrated by special transducers in the area of interest where the temperature reaches 55 °C causing coagulative necrosis of the affected tissue.…”
Section: High-intensity Focused Ultrasound (Hifu)mentioning
confidence: 99%